Galatians : Pentecostal commentary - Fee, Gordon D. (Blandford Forum, Dorset, UK : Deo Publishing, 2011)
Authorship -- Who were the Galatians? -- Date and place of writing -- Occasion / purpose and opponents -- Galatians as a letter -- The Holy Spirit in Galatians -- An outline of Galatians -- Galatians 1:1-9 : Introductory matters -- Salutation -- A curse on Paul's opponents -- Galatians 1:11-2:21 : Paul defends himself and his gospel -- The true source of Paul's gospel -- Paul's lack of relationship with Jerusalem -- Jerusalem affirms Paul's gospel -- Jerusalem reneges on Paul's gospel -- Paul's speech introduces his gospel -- Galatians 3:1-4:20 : The first argument from Scripture : The argument from Scripture -- Appeal to their experience -- Who are Abraham's true children? -- The law does not void the promise, plus : who is Abraham's "seed"? -- The role of the law -- First conclusion : Those in Christ are Abraham's seed -- The second conclusion : Those in Christ are God's true "sons"--The application : Do not return to slavery -- The Appeal : Return to your earthly brother / parent -- Galatians 4:21-5:12 : The second argument from Scripture -- The Scriptural data presented -- An interpretation of the Scriptural data -- The application of the Scriptural data -- Application and appeal : The danger of capitulating -- Second appeal : Condemnation of the agitators -- Galatians 5:13-6:10 : The Spirit supersedes the law -- The argument from Scripture -- The Application : The sufficiency of the Spirit -- Some specific examples of application -- The wrap-ups : doing good to all -- Galatians 6:11-18 : postscript : The opponents one more time.
Galatians 1:1-9 : introductory matters -- Galatians 1:11-2:21 : Paul defends himself and his gospel -- Galatians 3:1-4:20 : the first argument from Scripture -- Galatians 4:21-5:12 : the second argument from Scripture -- Galatians 5:13-6:10 : the Spirit supersedes the law -- Galatians 6:11-18 : postscript : the opponents one more time.
Includes bibliographical references (page 257) and indexes.
Keywords: Bible. -- Commentaries